A study on factors and strategies for digital innovation capability of normal vocational college teachers in China - Fu, Zhuoxin; Jiang, Man (Edelweiss Applied Science and Technology, 2026)
Based on the Technological Pedagogical Content Knowledge (TPACK) theory and digital innovation capability, this study aims to discuss factors affecting the promotion of digital innovation capability and possible methods for improvement. This paper focuses on teachers of Chinese higher vocational normal colleges as research subjects in studying the influencing factors and strategies for improving their digital innovation capability. Grounded in theories, this research adopts purposive sampling, selecting 12 faculty members at Chinese higher vocational normal colleges for focus group interviews, and 6 experts and scholars in the field of educational technology for semi-structured one-on-one interviews, in order to combine the viewpoints of ordinary teachers and administrators, and comprehensively collect data. The results demonstrate that the influencing factors include the individual, organizational, and macro levels. At the individual level, the factors include the TPACK gap and innovation mindset; the organizational level entails the research and development climate and platform facilities; while the macro level relates to assessment and evaluation systems.